2022
DOI: 10.1002/clen.202200284
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Food Waste into 3D Porous Carbon Traps for Selective Adsorption of Cationic Dyes

Abstract: Conversion of waste biomass into valuable functional materials accomplishes the concept of circular economy in the development of sustainable waste management, and also recovery of such resources possibly reduces the requirement of feedstocks. In this scenario, the development of methodologies toward the direct conversion of the raw biomass into solid adsorbent materials without the use of any templates is highly desirable, but exceptionally challenging due to the complexity of the process. Here the direct syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…After the adsorption by PC-900, the color of the mixture turned orange and only the adsorption peak at 464 nm can be observed, which indicated that MB had been almost removed from the mixture and only MO was left in the mixture. The above results intuitively indicated that when MO and MB simultaneously existed in the water, PC-900 had preferential adsorption for MB, which indicated a potential application of PC-900 in the separation of the mixed dyes. , …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…After the adsorption by PC-900, the color of the mixture turned orange and only the adsorption peak at 464 nm can be observed, which indicated that MB had been almost removed from the mixture and only MO was left in the mixture. The above results intuitively indicated that when MO and MB simultaneously existed in the water, PC-900 had preferential adsorption for MB, which indicated a potential application of PC-900 in the separation of the mixed dyes. , …”
Section: Resultsmentioning
confidence: 75%
“…The above results intuitively indicated that when MO and MB simultaneously existed in the water, PC-900 had preferential adsorption for MB, which indicated a potential application of PC-900 in the separation of the mixed dyes. 37,54 3.3.5. Regeneration Performance Study.…”
Section: Adsorption Selectivitymentioning
confidence: 99%